Identification of Ixodid Tick-Specific Aquaporin-1 Potential Anti-tick Vaccine Epitopes: An in-silico Analysis - Ndekezi, Christian; Nkamwesiga, Joseph; Ochwo, Sylvester; Kimuda, Magambo Phillip; Mwiine, Frank Norbert; Tweyongyere, Robert; Amanyire, Wilson; Muhanguzi, Dennis (Frontiers in Bioengineering and Biotechnology, 2019)
Ticks are arthropod vectors of pathogens of both Veterinary and Public health importance. Acaricide application which is currently the mainstay of tick control is hampered by high cost, the need for regular application and selection of multi-acaricide resistant tick populations. In light of this, future tick control approaches are poised to rely on integration of rational acaricide application and other methods such as vaccination. To contribute to systematic research-guided efforts to produce anti-tick vaccines, we carried out an in-silico analysis of tick aquaporin-1 (AQP1) protein in order to identify tick-specific AQP1 peptide motifs that can be used in future peptide anti-tick vaccine development. We carried out multiple sequence alignment (MSA), motif analysis, homology modeling, and structural analysis to identify tick-specific AQP1 peptide motifs. BepiPred, Chou & Fasman-Turn, Karplus and Schulz Flexibility, and Parker-Hydrophilicity prediction models were used to predict these motifs’ potential to induce B cell mediated immune responses. Tick AQP1 (GenBank ID: QDO67142.1) protein was largely similar to the bovine AQP1 (PDB:1J4N) (23 % sequence similarity; Structural superimposition of the homology model and 14JN homotetramers gave an RMSD=3.269 while superimposition of a single chain gave an RMSD=1.475). Tick and bovine AQP1 transmembrane domains were largely similar while their extracellular and cytoplasmic domain loops showed variation. Two tick-specific AQP1 peptide motifs; M7 (residues 106-125, p=5.4e-25), and M8 (residues 85-104, p=3.3e-24) were identified. These two motifs are located on the extracellular AQP1 domain. Motifs; M7 and M8 showed the highest Parker-Hydrophilicity prediction immunogenicity scores of 1.784 and 1.536 respectively. These two motifs can be a good starting point for development of potential tick AQP1 peptide-based anti-tick vaccines. Further analyses such as molecular dynamics, in vitro assays, and in vivo immunisation assays are required to validate these findings.